The plant programme - Plant, Jane (Virgin Publishing, 2001)
Professor Jane Plant's bestselling first book, Your Life in Your Hands, was aimed as those trying to treat or prevent breast or prostate cancer. In this book she and tellow scientist Gill Tidey show us how to make the necessary changes to implement the Plant Programme in our everyday life. From essential equipment in the kitchen, to weekly menu plans - delicious, nutritious, easy to prepare and mostly inexpensive - to food for the kids, The Plant Programme can be beneficial to everyone. Covering dining in, dining out and lifestyle aspects such as shopping, cleaning, gardening and grooming, the authors provide everything you need to know in a simple and easy-to-understand formula.